A randomized controlled trial: the effect of inulin on weight management and ectopic fat in subjects with prediabetes. Issue 1 (December 2015) - Guess, Nicola; Dornhorst, Anne; Oliver, Nick; Bell, Jimmy; Thomas, E.; Frost, Gary
Abstract Background Fat infiltration of the liver, muscle and pancreas is associated with insulin resistance and risk of diabetes. Weight loss reduces ectopic fat deposition and risk of diabetes, but is difficult to sustain to due to compensatory increases in appetite. Fermentable carbohydrates have been shown to decrease appetite and food intake, and promote weight loss in overweight subjects. In animal studies, fermentable carbohydrate reduces ectopic fat independent of weight loss. We aimed to investigate the effect of the fermentable carbohydrate inulin on weight maintenance, appetite and ectopic fat in subjects with prediabetes. Methods Forty-four subjects with prediabetes were randomized to 18 weeks' inulin or cellulose supplementation. During weeks 1–9 (weight loss phase) all subjects had four visits with a dietitian to guide them towards a 5 % weight loss. During weeks 10–18 (weight maintenance phase) subjects continued taking their assigned supplementation and were asked to maintain the weight they had lost but were offered no further support. All subjects attended study sessions at baseline, 9 and 18 weeks for measurement of weight; assessment of adipose tissue and ectopic fat content by magnetic resonance imaging and magnetic resonance spectroscopy; glucose, insulin and GLP-1 levels following a meal tolerance test; and appetite byad libitum meal test and visual analogue scales. Results Both groups lost approximately 5 % of their body weight by week nine (−5.3 ± 0.1 % vs −4.3 ± 0.4 %, p  = 0.13, but the inulin group lost significantly more weight between 9 and 18 weeks (−2.3 ± 0.5 % vs −0.6 ± 0.4 %, p  = 0.012). Subjects taking inulin had lower hepatic (p  = 0.02) and soleus muscle (p  < 0.05) fat content at 18 weeks compared to control even after controlling for weight loss and consumed less at thead libitum meal test (p  = 0.027). Fasting glucose significantly decreased at week nine only (p  = 0.005), insulin concentrations did not change, and there was a significant increase in GLP-1 in the cellulose group at 9 and 18 weeks (p  < 0.03, p  < 0.00001). Conclusion Inulin may have a two-pronged effect on the risk of diabetes by 1) promoting weight loss 2) reducing intrahepatocellular and intramyocellular lipid in people with prediabetes independent of weight loss. Trial registration Clinical trial number:NCT01841073 .